2006
DOI: 10.1002/ptr.1971
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of nitric oxide scavenging activity, In Vitro and Ex Vivo, of selected medicinal plants traditionally used in inflammatory diseases

Abstract: Steroidal and non-steroidal antiinflammatory drugs, despite their various side effects, are in great demand worldwide. Alternatively, herbal formulations provide relief to a large percentage of the population suffering from inflammatory diseases. Therefore, such practices need to be rationalized through a mechanistic approach. Thus, four traditional medicinal plants, namely Ventilago madraspatana Gaertn., Rubia cordifolia Linn., Lantana camara Linn. and Morinda citrifolia Linn. were selected for a study on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(60 citation statements)
references
References 14 publications
3
57
0
Order By: Relevance
“…Once generated, the NO interacts with oxygen and as a result nitrite is generated (Basu et al, 2006).…”
Section: Scavenging Activity Against Nitric Oxide (No)mentioning
confidence: 99%
See 2 more Smart Citations
“…Once generated, the NO interacts with oxygen and as a result nitrite is generated (Basu et al, 2006).…”
Section: Scavenging Activity Against Nitric Oxide (No)mentioning
confidence: 99%
“…Hence, the brain has a specifi c pathway to metabolize free radicals (Gaté et al, 1999;Mandelker, 2008) which infl uences the process of lipid peroxidation (Basu et al, 2006), the content of nitric oxide Ferreira et al, 2009) and the production of TBARS (Serafi ni et al, 2011).…”
Section: Determination Of In Vitro Antioxidant Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Assays of free-radical-scavenging activity with 1,1-diphenyl-2-picrylhydrazyl (Su et al, 2005;Yang et al, 2007), inhibition of copper-induced low-density lipoprotein oxidation (Kamiya et al, 2004), nitric oxide scavenging activity (Basu & Hazra, 2006) and quenching of H 2 O 2 (Chong et al, 2004;Jeffers et al, 2007) have been performed to evaluate the antioxidative effects of M. citrifolia L. and its products. Polyphenols, reducing glycosides (Calzuola et al, 2006), lignin derivatives (Su et al, 2005) and anthraquinones (Chong et al, 2004) have been suggested as sources of antioxidative activity in M. citrifolia L. However, there is little available information with which to quantitatively evaluate the antioxidative activity of M. citrifolia L ingredients.…”
Section: Fig 1 Unripe Fruitmentioning
confidence: 99%
“…The inhibition of NO is found to be a key mediator in the phenomenon of inflammation. Thus R. cordifolia was evaluated for inhibitory activity on NO produced in-vitro from sodium nitroprusside, and in LPS-activated murine peritoneal macrophages, ex vivo (Basu and Hazra, 2006). The inhibition of NO synthesis was correlated with the reduction of iNOS protein expression through Western blot.…”
Section: Anti-proliferative Propertymentioning
confidence: 99%